(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
The cytotoxic and antimicrobial activity of methanol crude extract and column fractions of the extract of the leaves of P. plebejum were examined by brine shrimp lethality bioassay and disc diffusion method respectively. The extracts showed significant cytotoxic as well as antimicrobial activities. Silica gel column chromatography of methanol extract of P. plebejum afforded a steroid. The structure was elucidated on the basis of spectral analysis, including 1H NMR and 13C NMR and also by comparing with data in the literature. Key words: Polygonum plebejum; Polygonaceae; Stigmasterol; Cytotoxicity. DOI: 10.3329/sjps.v2i2.5826 Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 66-71